Consumer culture theory - Belk, Russell W.; Sperry, John F. (Research in consumer behavior, 2007)
Drawing on a vast array of research contexts ranging from brand collecting, globalizing food in India, and art consumption to rock festivals, dog shows, and fan fiction, this volume suggests both the breadth and depth encompassed by Consumer Culture Theory (CCT). CCT is a specific interpretive approach to understanding consumer behavior that has crystallized in the past few years out of an evolving stream of research conducted over the past few decades. These chapters present cutting edge CCT research and are a subset of the work presented at the first CCT Conference. Besides its focus on consumption, CCT research emphasizes the cultural context of consumer behavior with the intent of constructing theory.As the innovative writings, photography, and poems in this volume illustrate, rather than being a single theory, Consumer Culture Theory is a set of empirical and conceptual approaches emphasizing non-positivist methods and culturally constructed meanings. These chapters present a rich stew of ideas, findings, and insights that represent the best of CCT. Together they sketch some of the domains that CCT research seeks to inform. Collectively they should enlighten, inspire, and empower further research in the CCT spirit. It is international in scope. It provides a qualitative and quantitative approach to consumer behavior research.